2014
DOI: 10.1007/s00251-014-0819-9
|View full text |Cite
|
Sign up to set email alerts
|

Different binding motifs of the celiac disease-associated HLA molecules DQ2.5, DQ2.2, and DQ7.5 revealed by relative quantitative proteomics of endogenous peptide repertoires

Abstract: Celiac disease is caused by intolerance to cereal gluten proteins, and HLA-DQ molecules are involved in the disease pathogenesis by presentation of gluten peptides to CD4+ T cells. The α- or β-chain sharing HLA molecules DQ2.5, DQ2.2, and DQ7.5 display different risks for the disease. It was recently demonstrated that T cells of DQ2.5 and DQ2.2 patients recognize distinct sets of gluten epitopes, suggesting that these two DQ2 variants select different peptides for display. To explore whether this is the case, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
92
0
4

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 88 publications
(105 citation statements)
references
References 40 publications
8
92
0
4
Order By: Relevance
“…To bind to HLA molecules, peptides need to conform to certain binding motifs. In celiac disease, the different HLA types that are associated with the disease haven been shown to have distinct peptide binding preferences, corresponding with different T-cell repertoires that are found in these patients [39,40]. The HLA-DQ2.5, HLA-DQ8 and HLA-DQ2.2 molecules all prefer negatively charged anchor residues that are introduced into gluten peptides through deamidation.…”
Section: Hla Bindingmentioning
confidence: 98%
See 3 more Smart Citations
“…To bind to HLA molecules, peptides need to conform to certain binding motifs. In celiac disease, the different HLA types that are associated with the disease haven been shown to have distinct peptide binding preferences, corresponding with different T-cell repertoires that are found in these patients [39,40]. The HLA-DQ2.5, HLA-DQ8 and HLA-DQ2.2 molecules all prefer negatively charged anchor residues that are introduced into gluten peptides through deamidation.…”
Section: Hla Bindingmentioning
confidence: 98%
“…This difference in epitope selection is governed by distinct binding specificity of the two HLA-DQ2 variants. Despite the fact that only one of the ten residues that differ between HLA-DQ2.2 and HLA-DQ2.5 makes contact with the peptide in the crystal structure of HLA-DQ2.5 with a bound gliadin epitope [41], the two molecules have widely different repertoires of endogenous peptides [39]. Peptides binding to HLA-DQ2.2 use P3 as a major anchor where there is preference for serine, threonine and asparatic acid.…”
Section: Hla Bindingmentioning
confidence: 99%
See 2 more Smart Citations
“…Moreover, peptide binding experiments indicated that Ser and Thr are anchor residues for binding of peptides to DQ2.2 but not to DQ2.5 [28,29]. This notion was further established by elution of endogenous peptides from B-lymphoblastoid cell lines [36]. This analysis revealed big differences in the repertoires of peptides eluted from DQ2.2 compared to DQ2.5, with a minority of peptides being presented by both HLA-DQ molecules.…”
Section: T-cell Epitopes Presented By Dq25 Dq22 and Dq8mentioning
confidence: 99%